LEARNING FROM THE PAST: THE USEFULNESS AND CHALLENGES OF ONLINE LEARNING - Ida Bagus Nyoman Mantra; I Gusti Ayu Putu Tuti Indrawati; I Nyoman Suwandi; Ni Luh Sukanadi; Anak Agung Rai Laksmi (Bajang Institute, 2021)
Recently online learning has been developed widely in Indonesia and most of the education institutions implemented online learning during the covid-19 pandemic. The purpose of online learning is to facilitate communication in the delivery of teaching materials in the field of education that is carried out remotely. It is generally intended for non-face-to-face teaching methods. This study was conducted to investigate the usefulness and the challenges encountered by the teachers in implementing online learning. This study made use of qualitative research design with descriptive analysis and to collect the data semi-structured interviews and online classroom observations were conducted to collect valid and reliable data. This study found that there was the usefulness of online learning which benefits students to improve their competence and also there were a number of challenges encountered by the teachers. Therefore, this study implies that teachers should acknowledge the challenges of online learning to create a better online learning activity.